Evolution Of Life - Time-Life Books (Time-Life Books : Hong Kong, 1994)
A richly illustrated survey of the history of life$1 (Bfrom its origins in early oceans through the rise of vertebrates, plants, and humanity$1 (Bwritten for a general audience. It includes full-colour photos, diagrams, timelines, and accessible narrative suitable for students and families.s
Keywords: Evolution